Territorial dynamics in the department of Cruz del Eje: scenarios of fragmented rurality - Paz, Magali Luciana (2023)
Introduction: The present research is based on the communes of the department of Cruz del Eje, within the arid region of the province of Córdoba (Argentina), in order to describe the different ways in which small units develop their production and social reproduction. Main Objective: To characterize the historical and current scenario in the communes of the department of Cruz del Eje within a regional economy of scarce development (such as that of the arid region of the province of Córdoba), in order to understand the socio-cultural practices of people with small productions and some of the public policies carried out in the territory. Method and technique: From a historical-anthropological approach and from a quali-quantitative triangulation (background review; statistical data and field work) the communal scenarios are studied in relation to the prevailing productive model and its impact on socio-territorial development. Results: The communal scenarios present conditions of vulnerability in the face of the advance of the agro-livestock frontier that is occurring in the region and such situation impacts in various ways the access to resources of those who work the small fruit and vegetable units. [Continue reading in the article]